Pengaruh Ekstrak Daun Nanas (Ananas comousus) Sebagai Green Inhibitor Terhadap Laju Korosi Baja Karbon Dalam Media Asam Klorida - Fauzia Mulyana; Komalasari Komalasari; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Corrosion is the deterioration of metals by chemical attack or interaction with its environment. The corrosion process is a natural phenomenon that cannot be stopped but can be prevented in many ways. The use of inhibitor is the best way to prevent metal from corrosion. Pineapple leaves are a green inhibitor that can be used to reduce the corrosion rate. This research aims to determine the concentration of tannin in pineapple leaves extract, the effect of variations in the concentration of corrosive media, the concentration of the inhibitor, the duration immersion against corrosion rate and inhibition efficiency of pineapple leaves extract. The soxhletation method was used to pineapple leaves extract with a ratio of solvent volume ethanol:aquadest 1:4. The test method carried out in this research is the weight loss method by using a variation of the concentration of the pineapple leaves extract (0, 0.5, 1.0 and 1.5 g/L) and the duration immersion (8, 16, 24, and 32 hours) in the concentrated hydrochloric acid solution 0.5M. The lowest corrosion rate in HCl solution 0.5M using inhibitor 1.5 g/L with duration of immersion 32 hours resulted 60.639 mpy and highest corrosion rate in HCl solution 1.0M without the addition of inhibitors with duration of immersion 24 hours resulted 530,659 mpy. It can be concluded that specimen with added higher the concentration of inhibitor in the lower concentration corrosive media yielded the corrosion rate to become lower in long immersion time. Keywords: corrosion rate, inhibitor, pineapple leaves